Outcomes and toxicities in patients with diffuse-large B cell lymphoma involving the gastrointestinal tract and digestive organs - Manzar, Gohar S.; Cha, Elaine E.; Corrigan, Kelsey L.; Yoder, Alison K.; Schrank, Benjamin R.; Nasr, Lewis F.; Chihara, Dai; Castillo, Luis Malpica; Nair, Ranjit; Jain, Preetesh; Neelapu, Sattva S.; Rodriguez, Maria A.; et al. (Frontiers in Oncology, 2024)
BackgroundDiffuse large B-cell lymphoma (DLBCL) involving the gastrointestinal (GI) organs is rare, and real-world outcomes after combined modality therapy (CMT) with systemic therapy (ST) and radiotherapy (RT) are not well-characterized, particularly in the contemporary era. We characterized outcomes in a large cohort of GI-DLBCL patients treated with ST alone or CMT.MethodsPatients with GI-DLBCL treated at a single institution were retrospectively reviewed. Kaplan-Meier and Cox regression models estimated survival. Multivariable analyses were conducted using the Cox proportional hazards model.ResultsOf 204 patients, gastric involvement was most common (63%). Most presented with early-stage disease (61%). All patients received ST and 65 patients (32%) received RT, 88% as part of first-line CMT. Median dose was 36 Gy (IQR 30.6–39.6) in 18 fractions (IQR 17–22). Median follow-up was 46 months. Five-year overall survival (OS) and progression-free survival (PFS) was 88% and 84%, respectively; complete response (CR) rate was 82%. Improved OS associated with low IPI (p=0.001), fewer chemotherapy lines (p<0.001), early stage (p<0.006), and CR (p<0.001). Survival did not differ by RT receipt (p>0.25). Only early stage and CR correlated with improved OS on multivariable analysis. Stomach-directed RT vs. RT to other sites correlated with improved PFS and OS (p<0.04). Patients with early stage DLBCL treated with CMT in the post-rituximab era had equivalent OS vs. ST alone, even with fewer chemotherapy cycles (p<0.02; median of 4 with RT vs. 6 cycles without). Fifty patients had bulky disease (≥7.5 cm), of whom 18 (36%) had early stage disease. Among patients with bulky disease, 5 (10%) developed relapse at the initial site of disease bulk. Four of the 5 patients did not receive consolidative radiation. Among these 4 patients, 3 relapsed only in their initial site of bulky disease. Of 191 patients with luminal GI-DLBCL, n=4 (2.1%) developed perforation; only one received RT. Acute Grade 3 toxicities were reported in 41.2% of patients, and 12 (5.8%) patients had late Grade 3 toxicities, 99% attributed to chemotherapy.ConclusionGI-DLBCL patients have favorable outcomes after CMT with minimal late toxicity. CMT may be offered with abridged systemic regimens with equivalent outcomes. Stomach directed-RT may mitigate relapse risk associated with incomplete disease response or bulky disease.